Feed and neurodegenerative diseases: a socio-scientific issue for developing argumentative skills - Cortés, María José; Rodríguez, Rodrigo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article shows the results of a research project whose objective was to promote the development of argumentative skills in a group of trainee teachers of the Chemistry degree program at the National Pedagogical University, through the design and application of a didactic unit on the implications of food chemistry in the development and prevention of the Parkinson’s disease [PD] as a socio-scientific issue. Activities such as open questions, discussion forums, and search for possible nutritional alternatives in the prevention and treatment for the PD were implemented. In each stage, the level of argumentation wasidentified, and the conceptual content of each argument was analyzed. It should be noted that the students were able to achieve a higher level of argumentation than the initial one by using the knowledge acquired in the solution and search for alternatives through active and reflective learning. They built arguments based on theoretical and experimental grounds on different aspects of this controversy.